Protocol description of the HOVON 141/VISION trial: a prospective, multicentre, randomised phase II trial of ibrutinib plus venetoclax in patients with creatinine clearance >= 30 mL/min who have relapsed or refractory chronic lymphocytic leukaemia (RR-CLL) with or without TP53 aberrations - Levin Mark-David; Kater Arnon P; Mattsson Mattias; Kersting Sabina; Ranti Juha; Tran Hoa Thi Tuyet; Nasserinejad Kazem; Niemann Carsten Utoft (BMJ PUBLISHING GROUP, 2022)
Introduction Literature is scarce on the combination treatment of ibrutinib and venetoclax (IV) is scarce in relapsed or refractory chronic lymphocytic leukaemia (RR-CLL). Especially, the possibility of stopping ibrutinib in RR-CLL patients in deep remission is unclear.
Methods and analysis In the HOVON 141/VISION trial, patients with RR-CLL are treated with 12 cycles of IV after a short induction with ibrutinib. Patients reaching undetectable minimal residual disease (uMRD) after 12 cycles of IV are randomised 1:2 to continue ibrutinib or stop treatment. The persistence of uMRD after stopping IV is studied. In addition, in patients who become positive for MRD again after stopping, IV treatment is reinitiated. The efficacy of this approach with regard to progression-free survival 12 months after randomisation is the primary endpoint of the study.
Ethics and dissemination This protocol respects the Helsinki declaration and has been approved by the ethical committee of the Amsterdam Medical Center. Study findings will be disseminated through peer-reviewed papers. All patients who fulfil the inclusion criteria and no-exclusion criteria, and have signed the informed consent form are included in the study.